The Combined Regulation of Long Non-coding RNA and RNA-Binding Proteins in Atherosclerosis - Ding, Yuanyuan; Yin, Ruihua; Zhang, Shuai; Xiao, Qi; Zhao, Hongqin; Pan, Xudong; Zhu, Xiaoyan (Frontiers in Cardiovascular Medicine, 2021)
Atherosclerosis is a complex disease closely related to the function of endothelial cells (ECs), monocytes/macrophages, and vascular smooth muscle cells (VSMCs). Despite a good understanding of the pathogenesis of atherosclerosis, the underlying molecular mechanisms are still only poorly understood. Therefore, atherosclerosis continues to be an important clinical issue worthy of further research. Recent evidence has shown that long non-coding RNAs (lncRNAs) and RNA-binding proteins (RBPs) can serve as important regulators of cellular function in atherosclerosis. Besides, several studies have shown that lncRNAs are partly dependent on the specific interaction with RBPs to exert their function. This review summarizes the important contributions of lncRNAs and RBPs in atherosclerosis and provides novel and comprehensible interaction models of lncRNAs and RBPs.